Combination of two methods for Legionella disinfection of water systems (cooling towers and potable water) in a Spanish hospital - Rivera, Jose-Maria; Aguiar, Juan-Manuel; Vos-Arenilla, Ana; Aguilar, Lorenzo; Gimenez, Maria-Jose; Granizo, Juan-Jose (International Journal of Infection Control, 2014)
This field study assesses the effectiveness of the installation of the Pastormaster system in potable water systems and a photo-catalyst in the cooling system as strategy for Legionella control in a Spanish hospital. Monthly, water samples were collected from taps in the Haematological Unit and the hospital cooling tower from 30-March-2005 to 31-December-2010. In the pre-installation period, all Legionella isolates from taps belonged to serogroups 2-14, and the isolation rate was 100% reduced after the Pastormaster system installation. In the cooling system, L. pneumophila serogroup 1 accounted for 80.0% of all Legionella isolates in the pre-installation period. After the photo-catalyst installation, isolation of L. pneumophila serogroup 1 was 57.2% reduced, but there was a significant increase in the isolation of Legionella isolates belonging to other serogroups or species. This study shows that the strategy implemented was highly effective in reducing serogroup 2-14 Legionella isolation from taps, thus potentially preventing nosocomial legionellosis, but not in reducing overall Legionella isolation in cooling towers.